2009
DOI: 10.1007/s00128-009-9674-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Glyphosate on Growth of Four Freshwater Species of Phytoplankton: A Microplate Bioassay

Abstract: The acute toxicity of glyphosate herbicide was tested on the four species of freshwater phytoplankton, Scenedesmus acutus, Scenedesmus subspicatus, Chlorella vulgaris and Chlorella saccharophila. Herbicide concentrations eliciting a 50% growth reduction over 72 h (EC(50)) ranged from 24.5 to 41.7 mg L(-1), whilst a 10% growth inhibition is achieved by herbicide concentrations ranging from 1.6 to 3.0 mg L(-1), difficult to find neither in paddy fields (it is not used in rice) nor in the lake of the Albufera Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 20 publications
2
26
0
1
Order By: Relevance
“…In toxicity tests analyzing the effect of glyphosate based herbicides on single species of diatoms and green algae, stronger negative effects on the diatom species ( Skeletonema costatum ) were observed (Tsui & Chu, 2003). Other studies found growth of S. quadricauda was inhibited when treated with an unspecified glyphosate-based formulation (Wong, 2000) or by treating four freshwater phytoplankton species with technical grade glyphosate (Vendrell et al, 2009). Since algae are able to produce mycosporine-like amino acids when stressed and this process can depend on the shikimate pathway (Shick & Dunlap, 2002), it is possible, that glyphosate-based herbicides lead to a decrease of the build up of these amino acids (Shick et al, 1999), probably also increasing the effects of temperature stress on algal communities.…”
Section: Discussionmentioning
confidence: 99%
“…In toxicity tests analyzing the effect of glyphosate based herbicides on single species of diatoms and green algae, stronger negative effects on the diatom species ( Skeletonema costatum ) were observed (Tsui & Chu, 2003). Other studies found growth of S. quadricauda was inhibited when treated with an unspecified glyphosate-based formulation (Wong, 2000) or by treating four freshwater phytoplankton species with technical grade glyphosate (Vendrell et al, 2009). Since algae are able to produce mycosporine-like amino acids when stressed and this process can depend on the shikimate pathway (Shick & Dunlap, 2002), it is possible, that glyphosate-based herbicides lead to a decrease of the build up of these amino acids (Shick et al, 1999), probably also increasing the effects of temperature stress on algal communities.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that microalgae are sensitive to a large scale of contaminants including heavy metals (Atici et al, 2008;MayerPinto et al, 2011;Wong and Chang, 1988), herbicides (Anton et al, 1993;Moro et al, 2012;Rioboo et al, 2002;Sáenz et al, 1997Sáenz et al, , 1993Sabater et al, 2002;Vendrell et al, 2009), insecticides (Gómez de Barreda Ferraz et al, 2004Carrasco, 2001a, 2001b;Wendt-Rasch et al, 2003) and industrial effluents (Tukaj et al, 1998;Walsh and Alexander, 1980). Even though studies on the effects of chlorpyrifos on microalgae are scarce, adverse effects have been reported both at cellular and population level.…”
Section: Introductionmentioning
confidence: 96%
“…This study showed also that the two Chlorella species were considerably more tolerant than the two Scenedesmus species isolated from Spanish rice fields. Vendrell et al (2009) tested the acute toxicity of glyphosate on S. acutus, S. subspicatus, C. vulgaris and C. saccharophila isolated from samples collected at Albufera lake in Valencia (Spain), one of the most important rice areas in Europe with a very rich flora and fauna. Although glyphosate is not applied to Valencian rice fields, its massive spraying in other agricultural crops surrounding the Albufera National Park (ANP), a protected ecosystem where rice is cultivated in harmony with local fauna and flora, is still a common practice.…”
Section: Herbicide Use and Predominant Weeds In Irrigated Rice Fieldsmentioning
confidence: 99%